2021
DOI: 10.52965/001c.24915
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Related Risk Factors for the Development of Lumbar Spine Adjacent Segment Pathology

Abstract: Individual risk factors for the development of adjacent segment pathology (ASP) need to be investigated and identified to address possible modifiable factors in advance and improve outcomes and reduce medical costs. This study aimed to review the literature regarding patient-related risk factors and sagittal alignment parameters associated with ASP development. MethodsThe authors performed an extensive review of the literature addressing the objectives mentioned earlier. ResultsCertain patient factors such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
0
3
0
3
Order By: Relevance
“…At present, most studies have focused on factors such as disc degeneration and spinal stenosis. Pinto et al [ 15 ] and Okuda et al [ 9 ] have confirmed that the preoperative sagittal direction of adjacent facet joints will affect the postoperative clinical efficacy, and when the tendency of bilateral facet joints increases, ASD and more serious clinical symptoms are more likely to occur following surgery. Furthermore, Choi et al [ 16 ] also demonstrated that patients with adjacent degeneration had more severe preoperative FJOA than those without adjacent degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…At present, most studies have focused on factors such as disc degeneration and spinal stenosis. Pinto et al [ 15 ] and Okuda et al [ 9 ] have confirmed that the preoperative sagittal direction of adjacent facet joints will affect the postoperative clinical efficacy, and when the tendency of bilateral facet joints increases, ASD and more serious clinical symptoms are more likely to occur following surgery. Furthermore, Choi et al [ 16 ] also demonstrated that patients with adjacent degeneration had more severe preoperative FJOA than those without adjacent degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Age, gender, obesity, previous degeneration, and hereditary characteristics all raise the probability of ASD. Sagittal alignment, in contrast, is important in the development of this disease [ 37 ]. Mean age, body mass index, cigarette smoking, blood pressure history, long segment fusion, high lumbosacral joint angle, pre- and postoperative L1-S1 sagittal vertical axis, postoperative lumbar lordosis, and preoperative pelvic incidence are all associated with the development of ASD according to a meta-analysis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abordaje (abierto, mínimo invasivo): una de las ventajas de los abordajes mínimamente invasivos es la preservación de la musculatura y del complejo ligamentario, es por ello que una disección amplia favorecerá la presencia de PSA. 1,23 Balance sagital (BS): el disbalance sagital (DS) (> 50 mm) se asocia al aumento de PSA. 13 Balance espinopélvico (BEP): al igual que el disbalance sagital, el disbalance espino pélvico (DEP) incrementa la sobrecarga de los segmentos adyacentes, la disminución de la lordosis lumbar (LL), incidencia pélvica (IP), y pendiente sacra (PS) incrementa el riesgo de PSA al igual que el aumento de la inclinación pélvica (InP).…”
Section: B Factores Dependientesunclassified
“…Sin embargo, el artrodesar uno o más segmentos se asocia con la presencia de la patología del segmento adyacente lumbar (PSAL), la cual es una causa importante de insatisfacción y discapacidad, motivo por el cual, si se identifican los factores de riesgo asociados, sería posible tomar consideraciones para prevenir y/o disminuir la presentación de la misma. 1 La PSAL engloba dos entidades: 1) Degeneración del segmento adyacente (DSA) y 2) Enfermedad del segmento adyacente (ESA).…”
Section: Introductionunclassified